Declarative particles in the Lao language of Luang Prabang: https://doi.org/10.69692/SUJMRD1001193 - Bountavong, Sonesanith; Sathamma, Phothong; Noyvongthong, khammonh; xaivongsan, Chanthaphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The research on the topic of Declarative particles in the Lao language of Luang Prabang aims to research to collect and record the declarative particles in the Lao language of Luang Prabang. The research method was to collect data with a sample group in various villages within the municipality of Luang Prabang, a total of 26 villages, with a total of 41 informants using interviews and participatory observation from actual conversations with the informants (sample group), and then analyze the data obtained with descriptive methods according to the set objectives. The research results found that: there are 25 words declarative particles such as ກະດາຍ /kada:j/, ກໍ /kɔ:/, ຈ້ອຍ /cɔ:j/, ຊີ້ /si:/, ຊໍ້າ /sam/, ເດ /de:/, ເດີ /də:/, ໄດ໋ /daj/, ດອກ /dɔ:k/, ແດ່ /dɛ:/, ຕີ່-ຕີ້ /ti/-/ti:/, ນ່າ-ໜາ /na:/, ເນາະ /nɔ/, ເນ /ne:/, ເນີ /nə:/, ພຸ້ນ /phun/, ຢູ່ /ju:/, ເຢີ /jə:/, ເລີຍ /lə:j/, ແຫຼະ /lɛ/, ແຫຼ້ວ /lɛ:w/, ຫວາ /wa:/, ຫຸ /hu/,ໂອ້ /ʔo:/, ຮະ /ha/.